Empowerment of Copra Farmer Group using E-Commerce - Johan Reimon Batmetan (JR Education, 2022)
Copra farmers in the village of Pondos, South Minahasa, are copra farmers who produce copra traditionally. So far, copra production has only been sold to existing middlemen and at a price determined by the middlemen themselves and regardless of the price of copra in the market. This causes the copra farmers to lose a lot of money because the farmers sell them at too low a price to existing middlemen or brokers. On the other hand, copra farmers do not have the skills to use e-commerce information technology so farmers are increasingly disadvantaged by middlemen. Another problem is that the market reached by copra farmers is only limited to the West Amurang area and is very limited, so the copra production produced by the farmers becomes abundant in the market. This is used by middlemen to speculate on prices so that copra prices fall and are very cheap among farmers. The solution that is trying to be offered is to provide training and assistance on the use of information technology, and e-commerce to copra farmers so that they are able to improve their ability to use e-commerce for marketing copra commodity products. With the increasing ability of copra farmers, they can use it to get copra prices that are in accordance with market prices, they are able to sell copra products through existing e-commerce and are able to reach a wider copra market. The method used to conduct training for copra farmers is a quantitative method of measuring the ability and income of farmers before and after the implementation of assistance. With this service program, it is hoped that copra farmers' skills and abilities in using e-commerce will increase and the income of copra farmers will increase because they are able to sell at market prices and can be monitored in real-time. The expected result is that copra farmers can reach a wide and large market for copra commodities so that they can increase farmers' copra production